Teori Negara Hukum dan Implementasinya dalam Sukuk - Sisi Ade Linda (Journal Islamic Economic and Bussines Studies, 2022)
Indonesia was one of the legal countries from its inception, when Indonesia proclaimed independence and sovereignty. The purpose of the state of law is to show legal sovereignty which means that the determinant and regulator in the administration of the state is law. This paper will discuss the theory of the legal state and its implications in sukuk. The research method used in this study is a qualitative method with a descriptive approach, which collects data related to sukuk in the ijarah contract taken from sources such as books, journals, skrpisi, thesis, and other related sources. The results showed that the theory of the state of law that is implicated in sukuk can be seen from the emergence of regulations related to sukuk, which is the purpose so that the implementation of sukuk is not disturbed and does not violate legal provisions. Thus this intercourse on sukuk is included in one of the examples of the application of legal theory..